The flowing waters vase. Iconography and meaning of a vessel from the Akkadian Period (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
The present paper aims to analyze the figurative theme of the flowing water vase starting from iconographic representations known in the glyptic production of the akkadian period (2350-2200 BC), when such a theme developed and spread. The focus is on the different modes of representation of this vessel, a methodological analysis drawing from various iconographic sources of glyptic production, with the aim of highlighting the symbolic value of such a vessel and the significance of the various characters, both mythical and heroic, associated with it.
Keywords: Water; Glyptic; Iconography; Akkadian Age; 3rd Millennium BCE; Mesopotamia